Gradual pressure-induced enhancement of magnon excitations in CeCoSi - Nikitin, S.E. (2020)
Fil: Franco, D.G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina; Max Planck Institute for Chemical Physics of Solids; Alemania